Treating Rheumatoid Arthritis by Genetically Engineered Biological Drugs: A Case Study.: Life Science-Rheumatic diseases - Nadezhda Vladimirovna, Zhuravleva; Olga Viktorovna, Sharapova; Liudmila Ivanovna, Gerasimova; Valentina Nikolaevna, Diomidova; Tatiana Lvovna, Smirnova; Nadezhda Dmitrievna, Ukhterova; Luiza Michailovna, Karzakova; Anastasia Vladimirovna, Arkhipova; Svetlana Alexandrovna, Yastrebova (International Journal of Life Science and Pharma Research, 2022)
The current modern treatment for Rheumatoid Arthritis is the genetically engineered biological drug rituximab. This drug helps to low the active rheumatoid arthritis. The aim of the study is to find and evaluate the clinical efficacy of rituximab . We present our own clinical observation of rituximab use in RA treatment of a female patient. We made the clinical assessment of the patient’s condition with the use of clinical, laboratory and instrumental methods. We made diagnostics with the use of the ACR/EULAR (American College of Rheumatology/European Alliance of Associations for Rheumatology) criteria. ESR, concentration of C-reactive protein, IgM of rheumatoid factor, antibodies to cyclic citrullinated peptide were determined. In 2007 the patient was diagnosed RA. She received the treatment with methotrexate, metipred, sulfasalazine, dexamethasone, cyclophosphamide, leflunomide, diprospan, non-steroidal anti-inflammatory drugs (NSAIDs). There was no effect. She had the total right & left knee joints arthroplasty. In 2009, according to blood tests she had: ESR according to Westegren is 90 mm/h, antibodies to cyclic citrulline-containing peptide (AB-CCP) is 500 U/ml, CRP 121.3 mg/l, RF 125.7 IU / ml. She had the diagnosis of rheumatoid arthritis, seropositive, grade 3 activity according to the DAS activity index 28 = 6.11 points with extra-articular manifestations (rheumatoid nodules) late stage, erosive (radiologically stage III), AB-CCP (+), FTS III. She started to receive rituximab therapy. Due to the durable inflammation, the secondary amyloidosis has started. At the same time the secondary systematic osteoporosis has started. We continued the rituximab therapy & zolendronic acid. The RA activity was low (according to the DAS index 28 = 2.95 points). In our study we found that the genetically engineered biological preparation (GEBP) rituximab is effective in the rheumatoid arthritis modern therapy.